Anticancer effects of PEP06 (TB01) in combination with Trifluridine/Tipiracil (TAS-102) in a xenograft model of human colorectal cancer - Ruohong Lin; Jiaxing Cheng; Jinlong Zhao; Liang Zhou; Jian Li; Xinchun Yang (Journal of Cancer Research and Clinical Oncology)
Abstract Background Colorectal cancer (CRC) is the third most common cancer globally, with advanced stages presenting significant treatment challenges. Recently years, drug combination therapy has become a promising strategy for cancer treatment. Objective To evaluate the therapeutic efficacy of the combination of the anti-angiogenic drug PEP06 (TB01) and the cytotoxic drug Trifluridine/Tipiracil (TAS-102) in human CRC HCT-116 xenograft mouse model. And quantitative assessment of the interaction between TB01 and TAS-102 in the treatment based on pharmacological effects. Methods This study utilized the human CRC HCT-116 xenograft nude mouse model to evaluate the antitumor effects of TAS-102 and TB01, both as mono-therapies and in combination therapies. Results The combination therapy not only demonstrated significantly inhibited tumor growth in a dose-dependent manner, but also seems to reduce the common toxicity associated with such treatments, as shown by the maintenance of body weights in the treated mice. Conclusion The synergistic effect observed from the combined use of TAS-102 and TB01 suggests a promising new treatment avenue for refractory CRC patients, meriting further investigation and potential clinical application.